Effect Combination Of Nitrogen Fertilizer And Weeding Frequency On The Growth And Harvest Of Chinese Cabbage - Tanasale, Vilma Laurien; Goo, Nureny; Patty, Christian W. (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2026)
Productivity of Chinese cabbage (Brassica rapa L.) often declines due to low nitrogen nutrient availability and high competition from weeds in cultivated land. The inappropriate application of nitrogen fertilizer doses can result in suboptimal plant growth, while uncontrolled weeds compete with crops for water, light, nutrients, and growing space. In addition, ineffective weeding frequency may inhibit growth and reduce the yield of Chinese cabbage. Therefore, this study was conducted to analyze the effects of nitrogen fertilizer dosage, weeding frequency, and their interaction on the growth and production of Chinese cabbage as a basis for improving crop cultivation management. The study employed a two-factor Randomized Block Design (RBD) with three replications. The factors consisted of nitrogen fertilizer dosage and weeding frequency treatments. The results showed that nitrogen fertilizer dosage and weeding frequency significantly affected the growth and production of Chinese cabbage. The N2P3 treatment (urea at a dose of 200 kg/ha combined with three weeding applications) produced the best results in suppressing weed growth and increasing Chinese cabbage production.